Competitive Advantage and its Supply Chain Strategy for Performance of Shipping Agents at Penang Port, Malaysia - Afifah Abd Razak; Shankar Chelliah (International Journal of Supply Chain Management, 2020)
The management of arrival and departure of ships at Penang Port needs the shipping agent for increasing global competitiveness and a source of income for developed countries. Of these, the primary purpose of this study is to analyse the relationship between competitive advantage, management knowledge, social networking and performance mediated by internationalization. A self-administered questionnaire was adopted to perform a systematic collection of data from shipping agents and shipping organisations in Penang Port. The partial least squares method was used for the conceptual framework of the study. In conclusion, the competitive advantage and performance of international shipping agents in Penang wellbeing at workplace and environment around. The presented research carefully developed and designed to fulfil the proposed objectives, but this study still has certain limitations. These limitations should be considered to accomplish practical research in the future. As mentioned, this study shipping agent a cross-sectional design. The authors believe that competitive advantage and performance of international shipping agents using empirical data from the port at Penang, as well as that this research is an important emerging topic for researchers, academicians and practitioners.Keywords—Competitive advantage, supply chain strategy, management knowledge, social networking, internationalization, government initiative and performance